Математична модель прогнозу ймовірності розвитку набутої міопії у дітей - Цибульська, Таміла Євгенівна; Tsybulska, T. E. (Одеса: Чорномор’я, 2019)
Незважаючи на досягнення сучасної науки в діагностиці міопії, залишаються труднощі для визначення пускових ланцюгів цього захворювання, особливо стосовно кожного індивідуального випадку. Для практичної роботи актуальним є створення математичної моделі, коли вже на первинному прийомі пацієнта лікар здатний спрогнозувати ризик розвитку набутої міопії у конкретного хворого. The model of the prognosis of the probability of development of acquired myopia in children included refractive corneal force, the axial length of the eye, the radius of curvature of the cornea, corneal diameter, the reserve of relative accommodation, the degree of connective tissue dysplasia, heredity of the disease. Classification ability of the model was determined according to the data of the training sample and amounted to 84.6%. At the same time, the probability of a positive positive result when using this model was 80.8 %, and the probability of a true negative result - 88.5%. The sensitivity of the model was equal to 87.5%, and the specificity was 82.1%. The evaluation of the quality of the model using the ROC analysis showed a good quality of the classification of characteristics: AUC was 0.897, p <0.0001 (95% CI 0.81-0.98).
The mathematical model of the prognosis of the probability of progression of acquired myopia in children
Keywords: матеріали конференцій